Exploring Recurrent Academic Expressions in Scientific Journal Articles and Their Functions in Supporting Academic Reading Comprehension - Faridatun Nida; Mayada Beni Pratiwi; Ahlan Cahya Purbanegara; Dini Riandini (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
University students need to be able to read article journal and comprehend the content in limited time. In fact, the surveys confirmed that the students face many challenges. However, the previous research only gave a clue of the effective strategy, that is by using keywords. Hence, this research is presented to provide the recurrent expressions written in journal articles as keywords to help the students find and understand the important information easier and quicker. The researchers also classify them based on its functions. The data was taken from sentences in the Abstracts of journal articles, considering that this subsection contains a summary of all parts, and utilizing the AntCont application. By collecting 100 Abstracts taken from 50 review articles and 50 research articles, the data was firstly identified by its common lexical bundle. Further, Genre Analysis theory was utilized to classify the functions of the bundles into the statement of purpose, method, and result. After completing the analysis, the researchers found that by identifying the keywords, not all of the bundle expressions were classified into one function. Several sentences were classified into the mixture of purpose and method, or method and result. Nonetheless, the identified keywords are predictably applicable and useful to help the students obtain the prominent information from a journal article. Therefore, the findings are applicable and beneficial for university students, or general reader of journal article, who need to implement the strategy of reading journal article by acknowledging the keywords.